2015
DOI: 10.1007/s00425-015-2320-6
|View full text |Cite
|
Sign up to set email alerts
|

A molecular physiological review of vegetative desiccation tolerance in the resurrection plant Xerophyta viscosa (Baker)

Abstract: Main conclusionProvides a first comprehensive review of integrated physiological and molecular aspects of desiccation toleranceXerophyta viscosa. A synopsis of biotechnological studies being undertaken to improve drought tolerance in maize is given.Xerophyta viscosa (Baker) is a monocotyledonous resurrection plant from the family Vellociacea that occurs in summer-rainfall areas of South Africa, Lesotho and Swaziland. It inhabits rocky terrain in exposed grasslands and frequently experiences periods of water de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 123 publications
(186 reference statements)
4
126
0
1
Order By: Relevance
“…Indeed, they both have a stabilizing effect on proteins and membranes in vitro, particularly trehalose, which finds practical application as a stabilizer for vaccines and other labile pharmaceuticals, allowing their storage and transport without refrigeration. Desiccation-tolerant resurrection plants accumulate massive amounts of trehalose or Suc when exposed to drought, and their cells remain viable despite losing $95% of their water content (Drennan et al, 1993;Iturriaga et al, 2000;Farrant et al, 2015). One way in which trehalose protects cells is by initiating controlled autophagy, thereby avoiding uncontrolled damage that would otherwise trigger programmed cell death (Williams et al, 2015).…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%
“…Indeed, they both have a stabilizing effect on proteins and membranes in vitro, particularly trehalose, which finds practical application as a stabilizer for vaccines and other labile pharmaceuticals, allowing their storage and transport without refrigeration. Desiccation-tolerant resurrection plants accumulate massive amounts of trehalose or Suc when exposed to drought, and their cells remain viable despite losing $95% of their water content (Drennan et al, 1993;Iturriaga et al, 2000;Farrant et al, 2015). One way in which trehalose protects cells is by initiating controlled autophagy, thereby avoiding uncontrolled damage that would otherwise trigger programmed cell death (Williams et al, 2015).…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%
“…Phylogenetic evidence suggests that vegetative DT in angiosperm resurrection plants represents an adaptation of developmentally regulated DT mechanisms in seeds that have been adjusted to the whole-plant context (Oliver et al, 2000;Illing et al, 2005;Rascio and La Rocca, 2005;Bartels and Hussain, 2011;Farrant and Moore, 2011;Farrant et al, 2015;Costa et al, 2017). Some similarities between seeds and angiosperm resurrection plants have been analyzed in the past (Illing et al, 2005), and the availability of more comprehensive desiccationassociated transcriptomes from resurrection plants (Rodriguez et al, 2010;Bartels and Hussain, 2011;Yobi et al, 2017) linked to sequenced genomes (Xiao et al, 2015;Costa et al, 2017) and seedlings in which DT is reintroduced (Maia et al, 2011;Terrasson et al, 2013;Costa et al, 2015) is allowing the exact mechanisms inherited by these plants to be refined.…”
Section: Information For Crop Improvementmentioning
confidence: 99%
“…Resurrection plants also experience a metabolic switch during dehydration. When water content drops below ;55% RWC, stomata close, carbon gain from photosynthesis ceases, and metabolism shifts from normal growth to cell defense and the accumulation of protective molecules, such as Suc, raffinose family oligosaccharides, and amino acids (Gechev et al, 2013;Farrant et al, 2015;Mladenov et al, 2015;Yobi et al, 2017). For instance, H. rhodopensis leaves start to accumulate Suc at ;60% RWC during desiccation in parallel with the significant consumption of glycolytic intermediates (Mladenov et al, 2015).…”
Section: Maintenance Of Cell Integrity Via the Accumulation Of (Solidmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus not surprising that resurrection plants have highly efficient antioxidant systems, which in turn have been proposed to be a valuable source of antioxidant potential for biotechnological applications both in plant stress tolerance as well as in the medicinal and cosmetic markets (Toldi et al 2009;Gechev et al 2014). Studies have shown that these comprise use of 'housekeeping' antioxidants (Illing et al 2005), often presenting unusual characteristics at low plant water contents (Farrant et al 2007(Farrant et al , 2012, as well as antioxidants such as 1-and 2-cys-peroxiredoxins, glyoxylase I family proteins, metallothionine-like antioxidants, oxidoreductases, several members of the aldehyde-dehydrogenases, and various polyphenols that are not typically highly expressed during dehydration of desiccation-sensitive material (reviewed in Farrant et al 2012Farrant et al , 2015Dinakar and Bartels 2013). Here, Govender et al (2016) report on a novel type II peroxiredoxin (XvPrx2) identified from the poikilochlorophyllous monocot resurrection plant Xerophyta viscosa, a species that has been relatively well characterised at the physiological and molecular levels (reviewed in Farrant et al 2015), and the genome of which has recently been sequenced .…”
Section: Desiccation-tolerant Extremophytesmentioning
confidence: 99%